2013
DOI: 10.1177/0363546513498990
|View full text |Cite
|
Sign up to set email alerts
|

Instability and Degenerative Arthritis of the Sternoclavicular Joint

Abstract: Injuries to the SC joint are uncommon. Recognition and classification of these injuries are critical to proper management, thus minimizing potential long-term sequelae such as posttraumatic arthritis and recurrent instability. Although nonoperative therapy is the modality of choice in anterior dislocations, posterior dislocations require special attention because of the presence of vulnerable posterior hilar structures. Surgical management of chronic instability and degenerative arthritis of the SC joint inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 46 publications
1
79
0
12
Order By: Relevance
“…Right-hand-sided injury occurred in 12 patients (54.5%). All dislocations were of Allman type 3, meaning they were all true dislocations rather than sprains (type 1) or subluxations (type 2) [22]. The mean age was 30 years (range 16-65) and the male-to-female ratio was 4.5:1.…”
Section: Resultsmentioning
confidence: 99%
“…Right-hand-sided injury occurred in 12 patients (54.5%). All dislocations were of Allman type 3, meaning they were all true dislocations rather than sprains (type 1) or subluxations (type 2) [22]. The mean age was 30 years (range 16-65) and the male-to-female ratio was 4.5:1.…”
Section: Resultsmentioning
confidence: 99%
“…His symptoms immediately improved by half. Based on this observation, the synovitis could have been secondary to the instability due to nonunion of the first sternocostal synchondrosis, since the clavicle, manubrium, and the first costal cartilage constitute the joint's articulation through being connected by the intra-articular ligament [12, 13]. Some authors have reported that CT is useful for diagnosing first rib injury [11, 14, 15].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the question of the type of reconstruction arises, which can in principle be achieved by means of a filament-augmentation of the ligament residues by seams or by replacing them with autologous tendon transplantation (24). The latter always entail a risk of complications at the donorsite of the tendons, which are widely known in the context of other ligament reconstructions such as at the knee or the ankle (25).…”
Section: Discussionmentioning
confidence: 99%